مطبوعة دروس في مقياستطبيق البرامجالاحصائيةفي الحاسوب - سعودي, أحمد (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2023)
أصبح لعلم الإحصاء دور كبير وأثر بالغ في مختلف العلوم خاصة مع التطور التكنولوجي المذهل وابتكار العديد من البرامج الإحصائية، وهو ما يتطلب إلمام كافة المتعاملين والباحثين في مختلف العلوم بأهمية الإحصاء والمعالجة الإحصائية وكيفية التعامل معها، والطرق العلمية لاستخلاص المؤشرات اللازمة للحكم على الظواهر والتنبؤ بها واتحاد القرارات المناسبة بشأنها. وبناء على كل هذا تم إعداد هذه المطبوعة البيداغوجية الموجهة إلى طلبة السنة الثانية ماستر تخصص علم النفس العمل والتنظيم وتسيير الموارد البشرية، بغرض بيان أهم المهارات الإحصائية التي يجب أن يمتلكها الباحث في هذا المجال، والتعرف على الأساليب والبرامج الإحصائية التي يصتخدمها والتدريب العملي عليها من خلال رصد الخطوات بالصور والشروح اللازمة. Statistics has become a major role and influence in various sciences, especially with the amazing technological development and the innovation of many statistical programs, which requires that all dealers and researchers in various sciences be familiar with the importance of statistics, statistical processing, how to deal with them, and scientific methods for extracting the necessary indicators to judge and predict phenomena and unite them.appropriate decisions regarding it. Based on all of this, this pedagogical publication was prepared, directed to second-year master’s students specializing in work psychology, organization, and human resources management, with the aim of explaining the most important statistical skills that a researcher must possess in this field, and learning about the statistical methods and programs that he uses and practical training on them through Monitor the steps with pictures and necessary explanations.